The Effect of Mobile Banking Service on the Saving Intentions of Generation Z - Maharani, Syifa Nadhira; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Over the last four years, Generation Z has shown little interest in saving. One of the reasons Jakarta's Generation Z has little interest in saving money is a lack of financial understanding. The aim of this research is to investigate, by employing dependent variables, the impact of the quality of Bank HIMBARA's mobile banking services on the saving interest of Generation Z from 2019 to 2023. This study used speed, security, trust, and utility as independent factors. Validity testing, reliability testing, hypothesis testing, and multiple linear regression are the analytical methodologies employed in this study, which used a sample of 130 members of Generation Z who had been using Bank HIMBARA's mobile banking for at least a year between 2019 and 2023.